Faktor-Faktor yang Berhubungan Dengan Motivasi Belajar Mahasiswa Semester VI di Program Studi DIII Kebidanan STIKes Fort De Kock Bukittinggi Tahun 2013 - ., Ermiza (Jurnal Martenity and Neonatal, 2017)
Quality is strongly influenced by the educational institution for the education system inputs such as students, faculty and infrastructure facilities supporting the teaching and learning process. These three factors are interdependent and influence in creating a successful learning process . Educational problems often faced by students include lecture schedule is not fixed , often have difficulty adjusting to the course , the lecturers , the order must be obeyed , campus environment , the burden of higher education costs . That difficulties in the face of conflict in motivating them to continue zealous in following the lecture . The purpose of this study was to determine the